2013
DOI: 10.3906/kim-1211-31
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-membered heterocycles using benzoylacetonitriles as synthon

Abstract: This review article represents a survey covering the synthetic strategies leading to 5-membered heterocycles.The reactions are subdivided into groups that cover the synthetic methods of those heterocycles, i.e. pyrroles, furans, thiophenes, pyrazoles, isoxazoles, thiazoles, and others, utilizing benzoylacetonitriles as starting precursor from 1985 up to the present. The reactions are subdivided into groups that cover the synthetic methods for those heterocycles from benzoylacetonitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our preliminary study involving the synthesis of 3-methyl-1H-pyrazol-5(4H)-one (1), 3-phenyl-1H-pyrazol-5-amine (2a) and 3-(4-chlorophenyl)-1H-pyrazol-5-amine (2b) were based on earlier reported procedures. 11,21,22 The catalyst free, one-pot, high yielding condensation reaction of 3-methyl-1H-pyrazol-5(4H)-one (1), 3-(4-substitutedphenyl)-1H-pyrazol-5-amines (2a-b) and aromatic aldehydes (3a-j) was carried out using methanol as a solvent at reflux temperature to furnish desired dipyrazolo [1,5- The reaction run at room temperature with constant stirring, gives a poor yield, what could be easily understanding taking in consideration a low solubility of 3-methyl-1H-pyrazol-5(4H)-one (1) in methanol at that temperature. Thus, we found that this MCRs reaction was more efficient under a reflux condition with utilization of an equimolar mixture of the starting materials in methanol, and good yields of the products were obtained after 3-5 hr.…”
Section: Chemistrymentioning
confidence: 99%
“…Our preliminary study involving the synthesis of 3-methyl-1H-pyrazol-5(4H)-one (1), 3-phenyl-1H-pyrazol-5-amine (2a) and 3-(4-chlorophenyl)-1H-pyrazol-5-amine (2b) were based on earlier reported procedures. 11,21,22 The catalyst free, one-pot, high yielding condensation reaction of 3-methyl-1H-pyrazol-5(4H)-one (1), 3-(4-substitutedphenyl)-1H-pyrazol-5-amines (2a-b) and aromatic aldehydes (3a-j) was carried out using methanol as a solvent at reflux temperature to furnish desired dipyrazolo [1,5- The reaction run at room temperature with constant stirring, gives a poor yield, what could be easily understanding taking in consideration a low solubility of 3-methyl-1H-pyrazol-5(4H)-one (1) in methanol at that temperature. Thus, we found that this MCRs reaction was more efficient under a reflux condition with utilization of an equimolar mixture of the starting materials in methanol, and good yields of the products were obtained after 3-5 hr.…”
Section: Chemistrymentioning
confidence: 99%
“…Moreover, the pyrazolo [3,4-c]pyrazole nucleus was proven to constitute the active part of several biologically active compounds [33][34][35][36][37][38]. On the other hand, the literature reveals that several methods have been described for the elaboration of substituted pyrazolo [3,4-c]pyrazoles [39] as reaction of 4-arylidenepyrazol-5-ones with hydrazines and hydrazides [40][41][42][43], Vilsmeier reaction of hydrazonopyrazol-5-ones, reaction of thiocarbohydrazides with 4-acetyl/benzoyl-pyrazol-5-ones [44], hydrazinolysis of aminocyanopyrazoles [45], hydrazinolysis of 5-oxo-N-phenyl-4,5-dihydro-1Hpyrazole-4-carbothioamides [46], reaction of amino and hydroxy pyrazoles with hydrazonyl halides [47], reaction of 5-chloro-1H-pyrazole-4-carbaldehydes with hydrazines in the presence of p-TsOH [48,49], and cyclocondensation of 4,5-dihydro-3-phenyl-5-[(2-propenyl)thio]-1H-1,2,4triazole with ethyl 2-chloro-2-(2-p-tolylhydrazono) acetate [50]. In view of the aforementioned facts, our efforts were directed towards a new facile synthesis of various functionalized derivatives of pyrazolo [3,4-c] pyrazole bearing coumarine moiety that have not been reported hitherto with the hope of augmentation in biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Gewald reaction has been extensively used in the pharmaceutical industry [12], it is quite surprising that no review emphasising the use of the Gewald reaction in dye chemistry has so far appeared. A few reviews have covered some aspects of the Gewald reaction [6][7][8][9][10][11][12][13][14][15][16][17], but none of the review has focused particularly on dye chemistry. The present review will focus on the use of Gewald chemistry in the synthesis of conventional and functional colourants, specifically azo dyes, fluorescent dyes (coumarin dyes, styryl dyes, thieno [2,3-d]pyrimidine dyes, bithiophene dyes), thiophene analogues of phthalocyanines, and fluorescent whitening agents.…”
Section: Introductionmentioning
confidence: 99%